Amomum subulatum: A treasure trove of anti-cancer compounds targeting TP53 protein using in vitro and in silico techniques - Ali, Sadaqat; Noreen, Asifa; Qamar, Adeem; Zafar, Imran; Ain, Quratul; Nafidi, Hiba-Allah; Bin Jardan, Yousef A.; Bourhia, Mohammed; Rashid, Summya; Sharma, Rohit (Frontiers in Chemistry, 2023)
Cancer is a major global health concern, and researchers are seeking innovative approaches to combat the disease. Clinical bioinformatics and high-throughput proteomics technologies have provided researchers with powerful tools to explore cancer biology. Medicinal plants are considered effective therapeutic agents, and computer-aided drug design (CAAD) is being used to identify novel drug candidates from plant extracts. The tumor suppressor protein TP53 is an attractive target for drug development, given its crucial role in cancer pathogenesis. In this study, we utilized a dried extract of Amomum subulatum seeds to identify phytocompounds that target TP53 in cancer. The extract was subjected to qualitative tests to determine its phytochemical composition. The team used diverse bioinformatics computational methods to evaluate the effect of Amomum subulatum and its natural components on TP53. These techniques included protein structural analysis, interactive comparison, alignment, and superposition of TP53 protein structures in 3D. We also conducted molecular docking and molecular dynamic (MD) simulation experiments to examine the binding interaction of the selected compounds with TP53. Based on virtual screening, the top three phytocompounds (tannins, saponins, and steroids) were selected based on their high binding energy and pharmacophore fit score. These compounds exhibited strong antioxidant activity and inhibited cancer cell inflammation in the TP53 pathway. MD simulations indicated that the ligand was bound to the protein with some significant conformational changes in the protein structure. This study provides novel insights into the development of innovative drugs for the treatment of cancer and inflammatory disorders. The use of medicinal plants in drug discovery is a promising area of research, and the findings of this study suggest that phytocompounds could serve as effective therapeutic agents for cancer and other diseases.